Development of high voltage pulse inducement method for biological cell - Mohamad Nazib, Adon; Mohd Noh, Dalimin, Prof. Dato' Dr.; Muhammad Mahadi, Abdul Jamil, Dr.; Norazan, Mohd Kassim (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/